Women’s performance as resistance to oppressive norms in Malachi Edwin Vethamani’s coitus interruptus and other stories - Mohd Rossdeen, Nur Syaqeera; Zainal, Zainor Izat (Universiti Putra Malaysia Press, 2020)
Malachi Edwin Vethamani published his first collection of short stories, Coitus Interruptusand Other Stories in 2018. Interestingly, nine out of twelve of his short stories dwell on themes related to homosexual men and womenâ€™s sexuality, and this not only attests to Vethamaniâ€™s skill as a storyteller, but also adds to the body of works by Malaysian writers which delve into queer experiences and womenâ€™s sexuality such as Dina Zamanâ€™s I AmMuslim (2007) and Jerome Kuganâ€™s Body 2 Body: A Malaysian Queer Anthology (2009). Vethamani has never identified himself as a feminist, yet in an interview with Mumbai Guide in September 2018, he admitted that he is particularly concerned with how institutions of Malaysian-Indian families deal with issues of gender, women and heterosexuality. In this study, we examine womenâ€™s resistance to accepted sexual roles and practices in three selected short stories in Coitus Interruptus and Other Stories: â€œCoitus Interruptusâ€, â€œIn Close Proximityâ€ and â€œThe Good Daughterâ€. These three short stories are selected because the protagonists are women and they share a central preoccupation with resisting sociallyconstructed gender roles and sexuality. Borrowing from Goffmanâ€™s dramaturgical analysis, we argue that women characters in the three selected stories are â€œperformingâ€ as a way to resist oppressive norms.